Assessing the Physiological Responses of Six Tree Species to Air Pollution in Pulogadung Industrial Area and UI Campus, Indonesia - Yuniati, Ratna; Putri, Ananda; Putrika, Afiatry (Scientific Research, New Technologies and Applications Vol. 4, 2024)
The present study assesses the Physiological Responses of Six Tree Species to Air Pollution in the Pulogadung Industrial Area and UI Campus, Indonesia. Air pollution is a global challenge that negatively affects both living organisms and the environment. Bioremediation using trees has emerged as an effective method for mitigating air pollution. Trees' responses to air pollution can be assessed using the Air Pollution Tolerance Index (APTI), which evaluates their physiological reactions. This study investigates the tolerance levels and physiological responses of six tree species—Mangifera indica (mango tree), Pterocarpus indicus (Burmese rosewood), Cerbera odollam (suicide tree), Pometia pinnata (Island Lychee, Matoa), Syzygium myrtifolium, (Red Lip), and Swietenia macrophylla (mahogany)—at the Pulogadung Industrial Estate in East Jakarta and UI Campus in Depok, based on their APTI values. Key environmental factors and APTI metrics, including relative water content (RWC), leaf extract pH, ascorbic acid content, and total chlorophyll content, were measured at both locations. Different plant species respond differently to air pollution, with some being tolerant and others sensitive. The classification of plants as tolerant or sensitive is based on APTI physiological parameters, including RWC, leaf extract pH, ascorbic acid content, and total chlorophyll content. Mangifera indica demonstrated the highest APTI score (9.79 ± 0.13) at Pulogadung Industrial Estate, reflecting a strong tolerance to air pollution. Conversely, Pterocarpus indicus showed the lowest APTI score (6.59 ± 0.18) at UI Campus, indicating sensitivity. The results suggest that tree species with higher tolerance levels have elevated RWC values and ascorbic acid concentrations, while those that are more sensitive exhibit lower RWC values and reduced total chlorophyll content. Further APTI research involving a broader range of tree species is recommended to obtain more comprehensive and accurate APTI values for a given location.